(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the public purchases destined to school feeding in an inland municipality of the state of Amazonas in 2020. An evaluative research was conducted with a mixed method based on the analysis of public notices and approval orders issued by the Municipal Education Bureau. A survey of quantities, values for acquisition, average prices and technical specifications of the purchased foodstuffs was carried out, with subsequent analysis of compliance with the normative acts in force for the management of the National School Feeding Program (PNAE). Results showed that natural or minimally processed foods were the items purchased in larger quantities, with average prices per kilogram lower than those recorded for processed and ultra-processed foods. The financial resources invested for purchases of food from family farming did not reach the minimum percentage of 30% required by the regulations in the PNAE. Most of the technical specifications for the acquisition of natural or minimally processed foods when the general attributes were evaluated, presented insufficient adequacies as determined by the legislation of the PNAE. All industrialized food products presented specifications with unsatisfactory adequacy to the nutritional composition and most of these foods presented insufficient adequacy to the packaging specifications. These results highlight the importance of the nutritionist’s performance as technical responsible in the management and execution of the PNAE, especially for the monitoring and participation in public procurement proposals following the regulations in force for school feeding and hygienic-sanitary quality of food in Brazil.